Estudo do crescimento de nanofios de ferro em superfícies vicinais usando a Teoria do Cristal Equivalente e o Método BFS - Wendell Simoes e Silva (2009)
Vicinal surfaces have been drawing the attention of condensed mattercommunity in the last few years because of their use in some activities ofhigh technological interest, namely: a) they are used in catalytic processes, such as, the ammonia oxidation on vicinal Pt catalyst; b) they have potential use in electronics because of the electron confinement on terraces induced by the potential barriers over steps and c) they are also used as templates in the self-organized growth of nano-structured systems with magnetic and conduction properties. Some theoretical methods have been used to investigate the properties of vicinal surfaces like DFT (Density Functional Theory) and EAM (Embedded Atom Method). However, the simulations based on these methods are computionally very demanding and the studies are often restricted to small systems. In this way, the possibility of using a fast and relatively accurate semiclassical method is very attractive. In this work we have used two semiclassical methods known as ECT (Equivalent Crystal Theory) and BFS (Bozzolo-Ferrante-Smith) method in order to study the relaxation trends and the alloy formation in vicinal surfaces, respectively. The multi-layer relaxation of Ag and Pt vicinal surfaces with high Miller-Index (p+1,p-1,p-1) were studied using the ECT methodology. The results obtained are in good agreement with ab initio calculations for all the terrace atoms except for the step atom. The simulations of Fe nanowire formation on Ag and Pt vicinal surfaces belonging to the (p+1,p-1,p-1) family were performed with the code developed by Dr Guillermo Bozzolo, one of the BFS Method creators. For comparison, we have also investigated the Fe alloy formation on Ag and Pt surfaces with low Miller-index (111) and (100). These surfaces are, respectively, the terraces and steps on the (p+1,p-1,p-1) vicinal surface family.